Mineral Depositions of Calcifying Skin Disorders are Predominantly Composed of Carbonate Apatite - Michael Franzen; Elena Moré; Janne Cadamuro; Josef Koller; Wolfgang Salmhofer; Iris Wohlmuth-Wieser; Cornelia Kronberger; Hermann Salmhofer (Acta Dermato-Venereologica, 2017)

(untitled)
Subcutaneous calcifications can lead to complications, including pain, inflammation, ulceration and immobilization. Studies on the pathophysiology of mineral compositions and effective treatment modalities are limited. We therefore studied 14 patients with subcutaneous calcifications. Mineral material was collected and analysed by Fourier transform infrared spectrometry. Blood analyses were run to evaluate systemic alterations of mineral metabolism. Carbonate apatite (CAP) was found to be the single constituent in the majority of patients (n = 9, 64.3%), 3 cases (21.4%) had a composition of CAP and calcium oxalate dihydrate and one case had a combination of CAP and magnesium ammonium phosphate, whereas CAP was the major component in all 4 cases. Only one case showed predominantly calcium oxalate. Thus, CAP was found to be the only or predominant component in most cases of subcutaneous calcifications. Chemical analyses of the mineral compositions may aid in the development of new treatment regimes to improve the solubility of mineral components and to decrease extraosseous calcifications.